Submerged Vegetation and Water Quality Degeneration From Serious Flooding in Liangzi Lake, China - Wang, Ligong; Han, Yuqin; Yu, Haihao; Fan, Shufeng; Liu, Chunhua (Frontiers in Plant Science, 2019)
In shallow lake ecosystems, flooding is a key disturbance factor of aquatic plants vegetation. Aquatic plants, especially submerged plants, play key roles in water ecosystems. Liangzi Lake experienced a severe flooding in July 2010, and the elevated water level lasted for three months. In this study, 10 transects with 120 monitoring points were set up for monthly monitoring during the three-year period encompassing before and after the flooding (2009–2011). The numbers, biomass and diversity of the submerged plants, as well as the physical and chemical characteristics of the lake water, were surveyed. There were 12 species belonging to 7 families and 7 genera in Liangzi Lake. 11 of the submerged plant species were found in 2009, but after the flood, that number decreased to 5 in 2011. The total biomass were significant differences among the three years (P < 0.05), with the largest biomass in 2009, and smallest in 2011. In 2009 and 2010, Potamogeton maackianus was the dominant species, but its dominant position had been weakened in 2011. After the flood, water transparency decreased, and the water depth, turbidity, total nitrogen, and total phosphorus increased. A redundancy analysis between the submerged plants and environmental factors found that the water transparency, turbidity and water depth were the key environmental factors affecting the plants. These results suggest that the long-lasting severe flooding of Liangzi Lake in 2010 led to the degradation of both the submerged plant community and water quality.